Empowering and Inspiring Young Girls a STEM at a Time: Using Place-Based Learning to Cultivate STEM Identities. Issue 1 (1st November 2021) - Winrow, Nevada; Winrow, Taylor-Symon; Jones, Michael B.; Heemsoth, Amy; Davis, Brian; Smith, David; Johnson, Dwayne K.
Black Girls Dive Foundation (BGDF) was established to empower and inspire young girls to explore their STEM (Science, Technology, Engineering and Mathematics) identities through aquatic-based STEM activities and ocean stewardship. BGDF's STREAMS program integrates aquatic-based recreation of SCUBA with scientific diving, ocean science, and stewardship. STREAMS explores ways to have broader reach and impact on STEM identity and STEM interest for individuals who are historically underserved and underrepresented in the sciences and provides research informed ways to close the divide and bring about equity.